THU0471 An Opportunity To Break The Fragility Fracture Cycle: 10 Months of A Fracture Liaison Service. (15th July 2016) - Rosa-Gonçalves, D.; Vieira, R.; Terroso, G.; Matos, R.; Pinto, R.; Vaz, C.; Costa, L.
Abstract : Background: A Geriatric Trauma Unit (GTU) was created in our hospital to optimize the acute treatment of patients with fragility fractures. The rheumatology department assists in subsequente evaluation of these. Objectives: To report the results of the evaluation after 10 months of a fracture liaison service (FLS). Methods: All patients over 65 years-old admitted to the GTU with a fragility hip fracture were systematically identified on a daily, prospective basis. The protocol was first implemented on March 2015 and we describe all patients included until December 2015. After a first evaluation during the hospital admission, patients are referred to the outpatient clinic for further characterization, generally within 3 months. The investigations included were dual-energy x-ray absortiometry (DXA, GE-Lunar), FRAX® including DXA and laboratory blood tests. A descriptive study was performed. Results: 208 cases of fragility hip fracture in patients above 65 years were identified, 78.9% women. Mean age (sd) of 83 years old (7.6). The most frequently affected segment of the hip was the trochanteric region (n=109, 52.4%), followed by the femoral neck (n=75, 36.1%). Most patients (68.8%) underwent surgical intervention within the first 48 hours. Regarding risk factors for osteoporosis (OP), there was a high prevalence of selective serotonin reuptake inhibitor consumption (n=40, 20.1%) as well as antiepileptics (n=10, 5%) and corticosteroids (n=9, 4.5%). Another highly prevalent risk factor was diabetes (n=49, 23.5%). Regarding the body mass index we found that the majority of patients (42.3%) had values within normal limits. Benzodiazepines use, clearly associated with falls, was reported by 44% of patients (n=91). In our analysis only 13.5% (n=28) of the patients had past or current use of bisphosphonates (BP) and only 5.8% of those reporting previous fragility fracture were ever treated for OP. The prevalence of previous fragility fracture was 25.3% (n=47), most commonly hip fracture (n=19, 10.2%). Prior to fracture, 62.5% of patients were independent for daily activities. However, within 3 months after the fracture, only 32% of these patients regain their autonomy. We have recorded 22 deaths, 12 cases during hospitalization. Full assessment of bone health was conducted in 44 patients. In 34% (15/44) of the cases, the densitometric criteria for OP were not met and 20 (45.5%) patients had radiographic signs of vertebral fragility fracture. Only 9 patients had 25-OH vitamin D levels above 30 ng/mL and 19 (43%) patients had deficiency levels. Using the FRAX toll, the absolute risk of major osteoporotic fracture was higher than 20% in 8 (18%) patients and the absolute risk of hip fracture was higher than 3% in 30 (68%) patients. Regarding treatment implementation, all patients received calcium and vitamin D supplementation and 35 (84%) patients started anti-osteoporotic treatment (33 BP and 2 denosumab). Conclusions: FLS are key pieces in the secondary fracture prevention as they facilitate patient care by automatically including all patients with a fragility fracture within a health-care system able to implement the adequate strategies to prevent future fractures as well as fracture-related complications. Disclosure of Interest: None declared